Perbandingan Hasil Belajar Sepak Bola Menggunakan Model Pembelajaran Kooperatif Tipe Jigsaw Pada Siswa Kelas XI SMK Negeri 8 Seram Bagian Barat - Sahetapy, Cristo Jessen Agustinus; Rumahlewang, Emma; Hattu, Mesak (Prgram Studi Pendidikan Jasmani Kesehatan dan Rekreasi, FKIP Universitas Pattimura, 2023)
This is comparative research, The variable was the comparison result of learning for Passing in the Football Game using the TGT and Jigsaw Learning Models for 25 students in class XI SMK Negeri 8 West Seram, Data sources come from teachers, students and researcher. Data collection techniques using observation, tests, and documentation or archives. the good results, and Very Good criteria (89-100), the TGT learning model amount to 4 students and the TGT Jigsaw learning model amount to 1. Explained in Figure 4.3. For obtain good criteria (77-88) the TGT learning model, were 13 students and the Jigsaw learning model, were 14 students. The sufficient criteria (65-76) for the TGT learning model are 6 students and the Jigsaw learning model is 10 students. Meanwhile (<=64) is only found in TGT with 2 students.